The Influence of Nearpod and Quizizz-Based Learning Media on Students' Mathematical Communication Skills at SMP Muhammadiyah 1 Cilacap - Natasya Cahya Kamila; Nida Ulfatunnisa (International Journal of Research in Mathematics Education, 2026)
Abstract: This research is motivated by the low mathematical communication skills of eighth-grade students at SMP Muhammadiyah 1 Cilacap. The researcher chose learning media to address the low mathematical communication skills of students. The purpose of this research is to analyze the influence of Nearpod and Quizizz-based learning media on the mathematical communication skills of eighth-grade students at SMP Muhammadiyah 1 Cilacap. This research is an experimental study with a quantitative approach and uses a quasi-experimental research design. The population in this study is all eighth-grade students at SMP Muhammadiyah 1 Cilacap, consisting of 5 classes. Sampling was done randomly using a convenience sampling technique, resulting in VIII IT class as the experimental class and VIII Bilingual class as the control class. Data collection in this study used a test instrument to measure students' mathematical communication skills. The data analysis technique used normality tests, homogeneity tests, and independent two-sample t-tests and Mann-Whitney tests. From the research results, it was concluded that Nearpod and Quizizz-based learning media have an influence on the mathematical concept understanding skills of eighth-grade students at SMP Muhammadiyah 1 Cilacap, with a significance value (2-tailed) of 0.000, which is less than 0.05.